Sex, sexuality and communication: a thematic analysis of the perceptions of young South African adults - Jordaan, Christina (Department of Communication Science, University of the Free State, 2007)
In South Africa, educators and parents, to a large extent, rely on educational sexuality programmes to teach adolescents and young adults the relevant aspects of sex and sexuality. It is argued that these programmes do not manage to address the understanding and interpreting of sexual language adequately. Most of these programmes focus on the biological, physical and social aspects of sex, paying attention to the “mechanics” of sex, the possible dangers of sex, effective protection against unwanted pregnancies, and sexually transmitted infections, but are silent on the language of sex and sexuality and also lack clear guidance on the interpretation and conveying of sexual interest. This article explores the perceptions of a sample group of 115 first year students registered for the Baccaulareus Educationis degree in primary school teaching at the Nelson Mandela Metropolitan University. A qualitative approach was used as research method and the research data was interpreted by means of a thematic analysis.
Keywords: Sex and sexuality; Educational sexuality programmes; Interpreting of sexual language